Entre fotografias e (in)visibilidades: análise da resposta brasileira de acolhimento aos Warao em Roraima a partir do método iconológico de Panofsky sob à luz dos direitos humanos - Gomes, Cárita Chagas (2023)
Photographies are capable of visually materializing knowledge, authority and arguments that would go unnoticed. Soon, evading the traditional legal normativism, the main focus of this thesis consists in analyzing the pictoric narrative around the Warao produced by the cell Comunicação Social da Força Tarefa Logística Humanitária de Roraima (FT Log Hum), looking to elucidate the visibility of this ethnic group in the legal response to the humanitarian refugee in Brazil. We seek, through an ethnically oriented perspective in respect for otherness, supporting the Human Rights, to understand the visibility of the Warao in the migratory context, considering the way in which they recognize themselves, how the host society recognizes them, and how the interaction of both takes place through mutual recognition, according to the regime of social type visibility. We interpreted, using the iconological method of Erwin Panofsky, photographic records of indigenous people of the Warao ethnic group registered, primarily, in the Venezuelan indigenous shelter Janokoida, in the city of Pacaraima, between 2018 and 2019, by Bruno Percut, 2nd Sergeant of the Brazilian Navy, member of said cell. In the end, we conclude that photography, like law, communicates through a language that encompasses the symbolism of human action, and therefore, propagates a certain way of perceiving that involves the combination of a social and historical organization model of the imagery perception that regulates vision functions and their various uses.